Epidermoid cyst in lower lip mimicking Keratoacanthoma: A rare case report - V. Tharani; Nandhini Gunasekaran; K.K. Raja; Ramesh Kumar A (Oral Oncology Reports)
Sebaceous cyst, which is otherwise called as epidermoid cyst, is a non-neoplastic cystic lesion lined by squamous epithelium with lots of keratin flakes in the cystic space. The commonest intra-oral site is the sublingual region (floor of the mouth) and it is very rarely seen in the lip region. Sometime when these lesions occur in the lip, they present diagnostic dilemma to the clinician. Although epidermoid cysts arising from the lower lip are rare, to avoid misdiagnosis, clinico-pathologic correlation is pivotal. This article presents a case of epidermoid cyst presenting in a rare location and clinically emulating as Keratoacanthoma.